2010
DOI: 10.1002/jso.21718
|View full text |Cite
|
Sign up to set email alerts
|

The expression of stem cell‐related indicators as a prognostic factor in human lung adenocarcinoma

Abstract: OCT4 and Bmi-1 may be good biomarkers to predict the prognosis of patients with completely resected lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 55 publications
2
17
1
Order By: Relevance
“…Bmi-1 is known to be a key regulator in the self-renewal of stem cells [36], and a recent report has shown that the expression of Bmi-1 in surgically resected specimens was a significant prognostic factor of a poor outcome in lung adenocarcinoma [20]. In our study, no obvious relation was seen between the expression of ABCG2 or Bmi-1 and patient outcome.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Bmi-1 is known to be a key regulator in the self-renewal of stem cells [36], and a recent report has shown that the expression of Bmi-1 in surgically resected specimens was a significant prognostic factor of a poor outcome in lung adenocarcinoma [20]. In our study, no obvious relation was seen between the expression of ABCG2 or Bmi-1 and patient outcome.…”
Section: Discussioncontrasting
confidence: 70%
“…A previous study reported that the expression of some CSC-related markers was related to a poor prognosis among patients with initially resected NSCLC, suggesting their potential use as prognostic markers such as CD133, ATP-binding cassette 6 superfamily G member 2 (ABCG2), Bmi-1, and Octamer-4 [20][21][22]. Indeed, CSCs are known to have drug or radiation-resistant features [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of Oct4 is restricted to pluripotent cells and its level decreases with the onset of differentiation and loss of pluripotency (9,15). In recent studies, Oct4 expression has been detected in various carcinomas including breast, prostate, bladder, head and neck squamous cell carcinomas and lung adenocarcinoma, which correlates with an unfavorable prognosis (16)(17)(18)(19)(20). Oct4 expression was only found in the immature neuroepithelium of high-grade immature teratomas, which indicates that Oct4 may be a promising biomarker for the diagnosis of highly malignant immature teratoma (21).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, BMI-1 expression has also been correlated with poorer patient outcomes [107, 121, 220], and amplification and concordant overexpression of the PcG, PHC3 , has recently been associated with poorer outcomes in NSCLC [221]. …”
Section: Prognostic Biomarkersmentioning
confidence: 99%